Testing the Usability of Company Websites - Małachowski, Andrzej (Testowanie użyteczności witryn internetowych, 2009)
A website is an important tool in developing company image and company identity; a new way to secure company share in e-commerce. As a unique ‘spot’ in a virtual space of an enterprise, it often decides on economic effectiveness of e-business and customer relations. A range of modern methods are presented, used in the evaluation of website utility and content. The tests allow for improving the functional and operational values of company websites in all phases of webpage lifespan – from initial design guidelines to everyday operation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 55, s. 234-241
Keywords: company websites; website usability; website life span